Manajemen Pengendalian Risiko dalam Upaya Mengurangi Non-Performing Loan Koperasi Simpan Pinjam di Kabupaten Sumedang - Hidayat, Udin; Hamdani, Dadan (E-Coops-Day, 2025)
Risk control management in an effort to reduce Non-Performing Loans (NPL) in the Sumedang Regency Savings and Loans Cooperative (KSP) was carried out for two days involving 30 participants from 15 cooperatives. This activity aims to increase the understanding and skills of KSP administrators in managing risks that can affect the financial health of cooperatives. The training, which was guided by Udin Hidayat as trainer and Dadan Hamdani as material writer, used learning methods that included theory, practice and group discussions. Evaluation results showed a significant increase in participants' understanding of risk management, with the average pre-test score increasing from 60% to 85% after the training. Participants succeeded in developing several risk mitigation strategies, such as improving the credit selection process and developing financial education programs for cooperative members. Feedback from participants shows that this training is very relevant and useful for KSP management. Based on the results of the training, it is recommended that KSP carry out follow-up actions through regular mentoring and evaluation sessions to ensure the implementation of the strategies that have been prepared. Apart from that, the development of continuing education programs for cooperative members is also highly recommended to increase awareness of financial responsibility. Thus, it is hoped that this training can contribute to reducing NPLs and improving the financial health of KSPs in Sumedang Regency in a sustainable manner.